2021
DOI: 10.3389/fneur.2021.735758
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study to Investigate Controlling Blood Pressure Under Transcranial Doppler After Endovascular Treatment in Patients With Occlusion of Anterior Circulation

Abstract: Objective: The objective of this study was to evaluate the effect of blood pressure (BP) management with transcranial Doppler (TCD) guidance in patients with large-vessel occlusion in the anterior circulation after endovascular thrombectomy (EVT) on the long-term prognosis.Methods: This was a prospective study; 232 patients were nonrandomized assigned to TCD-guided BP management (TBM) group or non-TCD-guided BP management (NBM) group. In the TBM group, BP was controlled according to TCD showing cerebral blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…42 Furthermore, evidence is scarce regarding BPV management as well. Radiological measures, including the assessment of recanalization status post-EVT, but also by evaluating dynamic brain autoregulation in real time though near-infrared spectroscopy-derived tissue oxygenation 43 or transcranial doppler 44 may also be used to guide BP management within targeted and tighter ranges, thus avoiding increased systolic BPV. Regarding antihypertensive treatment, calcium channel blockers and non-loop diuretic drugs either alone or as additives to other antihypertensive agents have been shown to significantly, albeit modestly, reduce BPV, whereas b-blockers have been associated with elevated BPV.…”
Section: Discussionmentioning
confidence: 99%
“…42 Furthermore, evidence is scarce regarding BPV management as well. Radiological measures, including the assessment of recanalization status post-EVT, but also by evaluating dynamic brain autoregulation in real time though near-infrared spectroscopy-derived tissue oxygenation 43 or transcranial doppler 44 may also be used to guide BP management within targeted and tighter ranges, thus avoiding increased systolic BPV. Regarding antihypertensive treatment, calcium channel blockers and non-loop diuretic drugs either alone or as additives to other antihypertensive agents have been shown to significantly, albeit modestly, reduce BPV, whereas b-blockers have been associated with elevated BPV.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, spectral analysis for rapid BPV assessment shows promise in promptly identifying at-risk patients without requiring lengthy BP recordings [110]. After identifying patients at risk, imaging techniques, such as the assessment of the collateral status [111][112][113] and the degree of recanalisation post-endovascular treatment [114,115] or the evaluation of the dynamic brain autoregulation in real-time using near-infrared spectroscopy-derived tissue oxygenation [116] or transcranial doppler [117], could guide BP management within targeted and tighter ranges to prevent increased systolic BPV.…”
Section: Blood Pressure Variability Among Patients With Acute Ischaem...mentioning
confidence: 99%
“…Although clinical studies have demonstrated the potential of portable MRI in complex clinical care settings ( Sheth et al, 2020 ), this device is not as sensitive to low-perfusion areas as professional perfusion imaging and is limited by a temporal window, preventing continuous tracking. The transcranial Doppler (TCD) technique allows for real-time evaluation of changes in cerebral hemodynamics and parenchymal structure through non-invasive measurement of CBF velocity ( Tao et al, 2021 ). However, the TCD method is effective in tracking perfusion of larger vessels and is less effective in detecting perfusion in small to medium-sized vessels and microvessels ( Gómez-Escalonilla et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%